Chromium-free metallized plastic current collector, preparation method thereof and lithium ion battery

Through the preparation method of chromium-free metallized plastic current collector, sodium silicate and phytic acid PA are used to form an electroplating protective layer, which solves the environmental pollution and process complexity problems in traditional chrome plating technology, and improves the performance and production efficiency of lithium-ion batteries .

CN119230839APending Publication Date: 2024-12-31JIANGSU THREE LAYERS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411330262.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The chromium used in traditional chrome plating technology, as a heavy metal element, leads to environmental pollution and health risks. The production process of ultra-thin electrolytic composite copper foil is complex and unstable, making it difficult to meet the needs of improved battery performance and reduced costs.

Method used

Using the preparation method of chromium-free metallized plastic current collector, Cu carrier foil and thickening layer are formed by magnetron sputtering and electrodeposition, and the electroplating solution containing sodium silicate, polyethylene glycol, phytic acid PA and CuSO4 is quickly formed. The protective layer is electroplated to form an insoluble PA-Cu composite as an intermediate layer, which enhances the bonding strength between the copper foil and the electrode material.

Benefits of technology

It significantly improves the capacity retention rate and rate performance of lithium-ion batteries, reduces environmental pollution, and has a fast and efficient process, which is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230839A_ABST
    Figure CN119230839A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of plating of metal materials, and particularly relates to a metallized plastic current collector, in particular to a chromium-free metallized plastic current collector, a preparation method thereof and a lithium ion battery, and the preparation method comprises the following steps: S1, pretreating a base material layer, and carrying out magnetron sputtering on Cu on the base material layer to obtain a carrier foil; s2, Cu is electrically deposited on the carrier foil through electro-deposition, and a thickened layer is obtained; s3, electroplating soaking is conducted through protection liquid, the deposition time is controlled to be 20 s, the deposition temperature is 35 DEG C, the current density is 1A / dm, and an electroplating protection layer is formed on the surface of the thickening layer; the electroplating protection layer is rapidly formed by matching direct current electroplating with the electroplating solution, and the protection layer formed by sodium silicate can isolate the metal surface from the outer layer of the electroplating protection layer in contact with a corrosion medium; the phytic acid PA and CuSO4 can form an insoluble PA-Cu2 + compound under the control of an electroplating process, and the insoluble PA-Cu2 + compound becomes an intermediate layer of an electroplating protective film, so that the bonding strength between the composite current collector copper foil and an electrode material is remarkably enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of plating metal materials, and specifically relates to a metallized plastic current collector, and in particular to a chromium-free metallized plastic current collector and a preparation method thereof, and a lithium ion battery. Background Art

[0002] In the current industrial manufacturing field, copper foil is a widely used basic material, and its surface treatment process usually involves chrome plating technology, which can significantly enhance its corrosion resistance and ensure the long-term stability and reliability of the material in harsh environments. However, this traditional practice is facing severe environmental challenges. Chromium, as a key component in the coating, is classified as a harmful heavy metal element. The pollution problems that may be caused by the chrome plating process and its subsequent waste treatment are contrary to the concept of green and sustainable development that is increasingly advocated around the world. This pollution will not only seriously threaten the balance of the ecological environment, but may also have long-term adverse effects on human health, which goes against the urgent need for modern society to transform into an environmentally friendly one.

[0003] In addition, with the continuous improvement of battery safety, energy density, cycle life and other performance, as well as the trend of battery cost reduction, copper foil, as a key auxiliary material for positive and negative electrodes of batteries, is developing in the direction of "thinness and lightness". At present, the production process of ultra-thin electrolytic composite copper foil below 6μm is complicated and the manufacturing process is unstable. Pure metal current collectors are no longer the best application carriers due to key factors such as cost, safety, and energy density.

[0004] Therefore, how to provide a method for preparing an ultra-thin current collector by replacing the chromium plating process is a technical problem that urgently needs to be solved in the art.

[0005] It should be noted that the above information disclosed in this background technology section is only used to understand the background technology of the present application concept, and therefore, the above description is not considered to constitute information of the prior art. Summary of the invention

[0006] The embodiments of the present disclosure at least provide a chromium-free metallized plastic current collector and a preparation method thereof, and a lithium-ion battery.

[0007] In the first aspect, the embodiment of the present disclosure provides a method for preparing a chromium-free metallized plastic current collector, comprising the following steps: step S1, pretreating a substrate layer, and magnetron sputtering Cu on the substrate layer to obtain a carrier foil; step S2, electroplating Cu on the carrier foil by electrodeposition to obtain a thickening layer; step S3, electroplating and immersing with a protective solution, controlling the deposition time to be 5-45s, the deposition temperature to be 10-45°C, and the current density to be 0.1-4A / dm 2 , forming an electroplating protective layer on the surface of the thickened layer.

[0008] In an optional embodiment, the substrate layer includes any one of PET and PP; the thickness of the substrate layer is 3 to 20 μm.

[0009] In an optional embodiment, the carrier layer has a thickness of 25 nm-50 nm.

[0010] In an optional embodiment, the thickness of the thickened layer is 500 nm-5 μm.

[0011] In an optional embodiment, the protective solution includes sodium silicate, polyethylene glycol, phytic acid PA, NaOH, CuSO4 and deionized water.

[0012] In an optional embodiment, the concentration range of the sodium silicate is 0.05g / L-1.25g / L; the concentration range of the polyethylene glycol is 0.25g / L-2.0g / L; the concentration range of the phytic acid PA is 4ml / L-30ml / L; the concentration range of the CuSO4 is 50g / L-300g / L.

[0013] In an optional embodiment, the NaOH is used to adjust the pH value of the protective solution, and the pH value of the protective solution ranges from 4 to 10.

[0014] In the second aspect, an embodiment of the present disclosure also provides a chromium-free metallized plastic current collector prepared by the method described above, comprising: a substrate layer; a carrier foil, a thickening layer and a plating protective layer stacked in sequence on both sides of the surface of the substrate layer; wherein the plating protective layer is formed on the surface of the thickening layer by a plating solution comprising sodium silicate, polyethylene glycol, phytic acid PA, NaOH, CuSO4 and deionized water.

[0015] In an optional implementation, the chromium-free metallized plastic current collector has a thickness of 4 to 30 μm.

[0016] In a third aspect, the embodiments of the present disclosure further provide a lithium-ion battery, comprising the chromium-free metallized plastic current collector as described above.

[0017] The beneficial effects of the present invention are that the chromium-free metallized plastic current collector and its preparation method, and the lithium-ion battery can quickly form an electroplating protective layer by using direct current electroplating in combination with an electroplating solution containing sodium silicate, phytic acid PA and CuSO4. The protective layer formed by sodium silicate can isolate the outer layer of the electroplating protective layer from contact between the metal surface and the corrosive medium. Phytic acid PA and CuSO4 can form an insoluble PA-Cu under the control of the electroplating process. 2+ The composite becomes the intermediate layer of the electroplating protective film, which significantly enhances the bonding strength between the composite current collector copper foil and the electrode material, and greatly improves the capacity retention rate and rate performance of the lithium-ion battery.

[0018] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention are realized and obtained by the structures particularly pointed out in the description, claims and drawings.

[0019] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 A schematic diagram of the structure of a chromium-free metallized plastic current collector provided in an embodiment of the present disclosure;

[0022] Figure 2 Surface SEM image of Comparative Example 1 provided in the embodiment of the present disclosure;

[0023] Figure 3 Surface SEM image of Example 1 provided for the embodiments of the present disclosure.

[0024] In the figure:

[0025] 1. Base material layer; 2. Carrier foil; 3. Thickening layer; 4. Electroplating protective layer. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] As used herein, the phrases "in one embodiment," "according to one embodiment," "in some embodiments," and the like generally refer to the fact that the particular feature, structure, or characteristic following the phrase may be included in at least one embodiment of the present disclosure. Therefore, a particular feature, structure, or characteristic may be included in more than one embodiment of the present disclosure, so that these phrases do not necessarily refer to the same embodiment. As used herein, the terms "example," "exemplary," and the like are used to "serve as an example, instance, or illustration." Any implementation, aspect, or design described herein as "example" or "exemplary" is not necessarily to be construed as preferred or superior to other implementations, aspects, or designs. On the contrary, the use of the terms "example," "exemplary," and the like is intended to present concepts in a concrete manner.

[0028] Herein, example embodiments of the present disclosure will be described in more detail with reference to the accompanying drawings. As used herein, expressions such as "at least one of..." modify the entire list of elements when following a list of elements, rather than modifying individual elements in the list. For example, the expression "at least one of a, b, and c" should be understood to include only a, only b, only c, both a and b, both a and c, both b and c, or all of a, b, and c.

[0029] The terms used herein are only used to describe specific exemplary configurations and are not intended to be limited. As used herein, the singular articles "one", "an" and "the" may also be intended to include plural forms, unless it is clearly indicated above that this is not the case. The terms "comprise", "include" and "have" are inclusive, and therefore specify the presence of features, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, elements, components and / or combinations thereof. The method steps, processes and operations described herein should not be interpreted as necessarily requiring them to be performed in the specific order discussed or shown, unless specifically identified as an execution order. Additional or alternative steps may be adopted.

[0030] Based on an in-depth study of environmental protection factors, we identified phytic acid as an environmentally friendly organic acid with significant application potential in the field of metal protection. Phytic acid can react with the metal surface to form a phytic acid conversion film with excellent corrosion resistance. In view of this, the present invention chooses to use phytic acid to treat the surface of the composite current collector copper foil in an environmentally friendly manner, in order to achieve the dual goals of improving the performance of the composite current collector copper foil and reducing environmental pollution. However, traditional phytic acid modification methods, such as impregnation methods, are usually time-consuming and difficult to meet the requirements of high efficiency and low cost in industrial production. In an actual industrial production environment, there is an urgent need for a fast and efficient processing technology to shorten the processing time and improve production efficiency. The defects in the above schemes are all the results obtained by the inventor after practice and careful study. Therefore, the discovery process of the above problems and the solutions proposed by the present disclosure for the above problems below should all be the contributions made by the inventor to the present disclosure during the disclosure process.

[0031] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.

[0032] Some embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0033] The present disclosure provides a method for preparing a chromium-free metallized plastic current collector, comprising the following steps: step S1, pretreating a substrate layer, and magnetron sputtering Cu on the substrate layer to obtain a carrier foil; step S2, electroplating Cu on the carrier foil by electrodeposition to obtain a thickening layer; step S3, electroplating and immersing the protective solution, controlling the deposition time to be 5-45s, the deposition temperature to be 10-45°C, and the current density to be 0.1-4A / dm 2 , forming an electroplating protective layer on the surface of the thickened layer.

[0034] In some embodiments, specifically, the substrate layer includes any one of PET and PP; the thickness of the substrate layer is 3 to 20 μm.

[0035] In some embodiments, specifically, the thickness of the carrier layer is 25 nm-50 nm.

[0036] In some embodiments, specifically, the thickness of the thickened layer is 500 nm-5 μm, preferably 800 nm-1.5 μm.

[0037] In some embodiments, specifically, the protective solution includes sodium silicate, polyethylene glycol, phytic acid PA, NaOH, CuSO4 and deionized water.

[0038] In some embodiments, specifically, phytic acid PA acts as a main passivator and antioxidant, forms a stable complex with the metal surface, provides antioxidant and corrosion resistance, and increases the conductivity and dispersion ability of the solution, which helps to form a uniform film on the surface of the composite current collector copper foil.

[0039] In some embodiments, specifically, CuSO4 is used to provide Cu 2+ Ion, Cu 2+ Reacts with phytic acid PA anions in the solution to form insoluble PA-Cu 2+ The composite material is deposited on the surface of the copper foil to form an intermediate layer of the electroplating protective film, which significantly enhances the bonding strength between the composite current collector copper foil and the electrode material.

[0040] In some embodiments, sodium silicate acts as a corrosion inhibitor and provides oxidation resistance at high temperatures, and the protective layer formed by sodium silicate helps to isolate the metal surface from contact with the corrosive medium.

[0041] In some embodiments, specifically, polyethylene glycol is used as a lubricant to make the surface of the passivation film smoother and more lustrous, and affects the reduction reaction in the electrochemical process and improves the deposition morphology of the metal.

[0042] In some embodiments, specifically, the concentration range of the sodium silicate is 0.05g / L-1.25g / L, preferably 0.15g / L-0.45g / L; the concentration range of the polyethylene glycol is 0.25g / L-2.0g / L, preferably 0.75g / L-1.25g / L; the concentration range of the phytic acid PA is 4ml / L-30ml / L, preferably 7.5ml / L-12.5ml / L; the concentration range of the CuSO4 is 50g / L-300g / L, preferably 70g / L-120g / L.

[0043] In some embodiments, specifically, the NaOH is used to adjust the pH value of the protective solution, and the pH value of the protective solution ranges from 4 to 10.

[0044] See also Figure 1 ,like Figure 1 As shown, the embodiment of the present disclosure also provides a chromium-free metallized plastic current collector prepared by the method described above, comprising: a substrate layer; a carrier foil, a thickening layer and a plating protective layer stacked in sequence on both sides of the surface of the substrate layer; wherein the plating protective layer is formed on the surface of the thickening layer by a plating solution including sodium silicate, polyethylene glycol, phytic acid PA, NaOH, CuSO4 and deionized water.

[0045] In some embodiments, specifically, the thickness of the chromium-free metallized plastic current collector is 4-30 μm.

[0046] The disclosed embodiment also provides a lithium-ion battery, comprising the chromium-free metallized plastic current collector as described above.

[0047] In some embodiments, specifically, the electroplating solution is configured and the electroplating process parameters are set according to the parameters described in Table 1 below, and the results are shown in Tables 1 and 2.

[0048] Table 1 Parameters and performance of Examples 1-9 and Comparative Example 1

[0049]

[0050] Table 2 Parameters and performance of Examples 10-13

[0051]

[0052] Corrosion resistance test: After immersing in an electrolyte containing 1000 ppm water for 240 h, the corrosion resistance of the original metallized plastic current collector copper foil and the PA-Cu metallized plastic current collector copper foil was evaluated, and their surface morphology was observed.

[0053] In some embodiments, specifically, from Examples 1 to 13 and Comparative Example 1, it is known that: Figure 2 As shown in FIG. 1 , after being immersed in the electrolyte in Comparative Example 1, the surface of the original metallized plastic current collector copper foil is covered with many spherical particles, which are corrosion products in the electrolyte, resulting in a rough surface. Figure 3 As shown, the surface of the PA-Cu metallized plastic current collector copper foil immersed in the electrolyte in Example 1 is relatively smooth, which indicates that the PA-Cu film is more stable in the electrolyte than the original copper foil.

[0054] Peel strength test: used to evaluate the bonding strength between copper foil and active material. 80% artificial graphite powder, 10% conductive carbon black and 10% polyvinylidene fluoride were mixed in proportion, and then an appropriate amount of N-methylpyrrolidone (NMP) was added under stirring to obtain a uniform slurry. The slurry was evenly applied to the surface of the original metallized plastic current collector copper foil and the PA-treated metallized plastic current collector copper foil with a scraper. Then, the coated electrode sheet was dried in a vacuum oven at 60°C for 12 hours to test its adhesion.

[0055] In some embodiments, specifically, from Examples 1-13 and Comparative Example 1, it is known that the bonding strength between graphite particles and the original metallized plastic current collector copper foil is 0.35 N / cm, while the bonding strength with the PA-Cu metallized plastic current collector copper foil is greater than 0.35 N / cm. Obviously, the bonding strength between the PA-Cu foil and the active substance is significantly increased, which is the result of the interaction between certain active groups (such as hydroxyl groups) in the PA molecule and the organic matter in the active substance. The PA film can be used as a coupling agent to enhance the bonding strength between the active substance and the copper foil.

[0056] In summary, the chromium-free metallized plastic current collector and its preparation method, and the lithium-ion battery use direct current electroplating with an electroplating solution containing sodium silicate, phytic acid PA and CuSO4 to quickly form an electroplating protective layer. The protective layer formed by sodium silicate can isolate the metal surface from the contact with the corrosive medium. The phytic acid PA and CuSO4 can form an insoluble PA-Cu under the control of the electroplating process. 2+ The composite becomes the intermediate layer of the electroplating protective film, which significantly enhances the bonding strength between the composite current collector copper foil and the electrode material, and greatly improves the capacity retention rate and rate performance of the lithium-ion battery.

[0057] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A method for preparing a chromium-free metallized plastic current collector, characterized in that: The steps include: Step S1, pretreating the substrate layer and magnetron sputtering Cu on the substrate layer to obtain a carrier foil; Step S2, electrodepositing Cu on the carrier foil by electrodeposition to obtain a thickened layer; Step S3, electroplating with protective solution, controlling the deposition time to be 5-45s, the deposition temperature to be 10-45°C, and the current density to be 0.1-4A / dm 2 , forming an electroplating protective layer on the surface of the thickened layer.

2. The method for preparing a chromium-free metallized plastic current collector according to claim 1, characterized in that: The substrate layer includes any one of PET and PP; The thickness of the substrate layer is 3-20 μm.

3. The method for preparing a chromium-free metallized plastic current collector according to claim 1, characterized in that: The thickness of the carrier layer is 25nm-50nm.

4. The method for preparing a chromium-free metallized plastic current collector according to claim 1, characterized in that: The thickness of the thickened layer is 500nm-5μm.

5. The method for preparing a chromium-free metallized plastic current collector according to claim 1, characterized in that: The protective solution comprises sodium silicate, polyethylene glycol, phytic acid PA, NaOH, CuSO4 and deionized water.

6. The method for preparing a chromium-free metallized plastic current collector according to claim 5, characterized in that: The concentration range of the sodium silicate is 0.05 g / L-1.25 g / L; The concentration range of the polyethylene glycol is 0.25 g / L-2.0 g / L; The concentration range of the phytic acid PA is 4ml / L-30ml / L; The concentration range of CuSO4 is 50g / L-300g / L.

7. The method for preparing a chromium-free metallized plastic current collector according to claim 5, characterized in that: The NaOH is used to adjust the pH value of the protection solution, and the pH value of the protection solution ranges from 4 to 10.

8. A chromium-free metallized plastic current collector prepared by the method according to any one of claims 1 to 7, characterized in that: include: substrate layer; The carrier foil, the thickening layer and the electroplating protective layer are sequentially stacked on both sides of the surface of the substrate layer; The electroplating protective layer is formed on the surface of the thickened layer by an electroplating solution including sodium silicate, polyethylene glycol, phytic acid PA, NaOH, CuSO4 and deionized water.

9. The chromium-free metallized plastic current collector according to claim 8, characterized in that: The thickness of the chromium-free metallized plastic current collector is 4-30 μm.

10. A lithium ion battery, characterized in that: The invention comprises a chromium-free metallized plastic current collector as described in any one of claims 8 to 9.